2015
DOI: 10.1177/0020764015575799
|View full text |Cite
|
Sign up to set email alerts
|

Type of unit and population served matters when implementing a smoke-free policy in mental health settings: Perceptions of unit managers across England

Abstract: in mental health settings: Perceptions of unit managers across England. AbstractBackground: Globally, smoking remains a significant issue for mental health populations. Many mental health trusts in England are facing challenges of implementing the NICE guidance according to which all mental health settings, no matter the type, should be entirely smoke-free and provide comprehensive smoking cessation support. Aim:To determine if unit type and unit manager smoking status influence mental health smokefree policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Finally, because of low numbers of participants in each type of treatment setting, differences were not highlighted. Further research is warranted given the different practices and cultural contexts to treatment provision across types of programs, and recent research, which has found variation in mental health treatment settings [25].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, because of low numbers of participants in each type of treatment setting, differences were not highlighted. Further research is warranted given the different practices and cultural contexts to treatment provision across types of programs, and recent research, which has found variation in mental health treatment settings [25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to facilitating the implementation process with teaching and training of staff to be able to handle the new activities, also staff and managerial attitudes (27;28) and individual lifestyle are surprisingly important for successful implementation of HP (28). Interestingly, the patients are positive towards new interventions, and especially positive to being offered HP services as an integrated part of patient pathways (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has been argued that partial smoking bans in conjunction with smoking cessation support should be considered as a harm minimization approach (National Mental Health Consumer and Carer Forum, ). However, partial smoking bans have been shown to create more problems and often result in inconsistent enforcement of the policy (Lawn & Campion, ; Sohal, Huddlestone & Ratschen, ; Zabeen et al ., ). Additionally, comprehensive bans may be associated with improved smoking outcomes for patients relative to partial bans (Stockings et al ., ).…”
Section: Critical Examination Of Arguments Against Smoke‐free Mental mentioning
confidence: 97%
“…Allowing patients to smoke during limited periods increases persistence of nicotine withdrawal, undermines recognition of nicotine dependence as substance abuse and perpetuates a culture of smoking which inadvertently implies it is ‘too hard’ to support this population to manage their smoking behaviour (Moss et al ., ; Prochaska, ; Zabeen et al. ).…”
Section: Critical Examination Of Arguments Against Smoke‐free Mental mentioning
confidence: 99%